Earnings Management, Board Independence And Audit Fees Considering The Firm’s Profitability Level - Moradi, Javad; Valipour, Hashem; Pahlavan, Zahra (Asian Economic and Financial Review, 2012)
This study investigates the relation between earnings management, board independence and audit fees considering the firm’s profitability level. Two main hypotheses have been designed by theoretical framework, and have been tested on 57 listed companies in Tehran Stock Exchange during 2003 to 2009. The statistical analysis had been done by multi-variable regression analysis and one-way ANOVA analysis, too. The findings show that there is a meaningful and positive relation between earnings management and audit fees. Also, there is a meaningful and negative relation between board independence and audit fees. The results suggest that the higher the level of profitability, the higher the audit fees.